A strict definition of homoeopathy according to Hahnemann - Adler, U.C.; Ambrosio, E.; Anelli, I.M.; Cappello, E.; De Toledo Cesar, A.; Guimarães, E.C. (British Homeopathic Journal, 1996)
A review of classical and contemporary textbooks showed that although the term homoeopathy is widely known and used, it remains ambiguous and vague. In an attempt towards clarification we present a review of Hahnemann's definition of the term and conclude that it refers to the outcome of interaction between two different vital affections which, however, have very similar effects on living organisms. We found that Hahnemann used examples to demonstrate the homoeopathic phenomena and postulated that homoeopathy could exist without experimental provings in healthy individuals, infinitesimal doses, dynamization and single medicines, all of which are fundamental elements in his methodology. We also discuss the benefits of using one strict conceptual definition of homoeopathy. This can contribute to recognition of the homoeopathic phenomenon in nature and in medical practice.
Keywords: Homoeopathy; Hahnemann's definition